Menthol mouth rinsing does not improve strength or power performance - Best, R.; Temm, D.; Hucker, H.; McDonald, K. (Sport and Exercise Science New Zealand, Palmerston North, 27-29 November 2019, 2019)
Capsaicin ingestion has been shown to improve strength performance, possibly due to its analgesic effects and ability to facilitate Ca2+ release from the sarcoplasmic reticulum. Menthol, a capsaicin antagonist, has similar analgesic properties to capsaicin and may also have a depolarising effect upon membranes - hence, we investigated the effect of menthol mouth swilling upon strength and power performance. Methods Nineteen (10 male; 9 female) participants undertook three attempts of an isometric mid-thigh pull (IMTP), vertical jump and six-second Wingate. Recovery between all efforts was three minutes, with participants undertaking a familiarisation session prior to experimental trials (control; menthol) which were performed in a randomised, counterbalanced order. Testing order was kept consistent so as to minimise any variance due to post-activation potentiation. Standardised mean differences were calculated (Cohen`s d) to quantify the magnitude of between condition differences, and interpreted as follows: 0 - 0.2 Trivial, 0.2 - 0.6 Small, 0.6 - 1.2 Moderate and > 1.2 Large. Results Small differences between familiarisation and experimental trials were found across IMTP and vertical jump trials, whereas with Wingate performance familiarisation only trivially differed to control and menthol. Control and menthol trials were trivially different across all metrics. Take home message Menthol swilling does not improve repeated strength of power performance, following a familiarisation trial.